Die reaksies 48, 50Ti ([rho,rho'gamma])48, 50Ti BY Ep = 6 MeV EN 48, 50Ti([alfa,alfa'gamma])48, 50Ti BY E[alfa] = 12 MeV - Van Waart, J.(Johannes) (Stellenbosch : Stellenbosch University, 2012)
In die titel is die 48 en 50 in superskrif.